SYNTHESIS AND CHARACTERIZATION OF HEMATITE (Fe2O3) EXTRACTED FROM IRON ORE BY PRECIPITATION METHOD - Andia Andia; Adi Rahwanto; Zulkarnanin Jalil (Jurnal Natural, 2016)
Indonesia has a lot of mining material of iron ore that could be used for various purposes in the steel industry or for other. This research, has synthesized and characterization of hematite from local iron ore from Lhoong area by precipitation mechanism. The iron ore powder was magnetic separation with magnet then mixed with HCl and NH4OH. Then, it was dried at temperature of 150 ºC and calcinated at 500º C for 2 hours. Characterizations were perfomed using X-ray Diffraction (XRD) and X-ray Fluorescence (XRF). As the results, it was found that the magnetic separation iron ore showed the composition of Fe2O3 (95.99%), SiO2 (2.10%). Then, by precipitation mechanism, the composition of Fe2O3 found around 96.58%. Next, the synthesis result are characterized with XRD show that the main phase is dominan in iron ore of Lhoong is hematit (Fe2O3). Scherrer calculations showed that precipitation mechanism to reducing grain size, the process of magnetic separation (58.009 µm) and the precipitation mechanism (20.950 µm.)